Who's Auditioning Who? Applicant-Reported Elements of the Best and Worst Plastic Surgery Subinternships. Issue 4 (23rd February 2022) - Wickenheisser, Victoria A.; Langdell, Hannah C.; Brown, David A.; Phillips, Brett T.
Abstract : Background: Many integrated plastic surgery applicants choose to complete one or more visiting subinternships or "away rotations" at programs outside of their home institution. As these rotations are so critical on both sides of the application process, the authors sought to identify the factors that influence subinternship experiences for plastic surgery applicants. Methods: A survey was used to collect information about demographics, the subinternship experience, and interview preferences. The survey was distributed to current plastic surgery interns and applicants who applied to Duke Plastic Surgery in the 2019/2020 application cycle. Results: One hundred forty-two responses were received (response rate, 35.2 percent). The mean number of subinternships completed was 4.47. The defining feature of respondents' best subinternship most often included engagement from faculty and residents, autonomy, and integration with the team. The worst feature of respondents' worst subinternship experience most often included a sense of disinterested or "malignant" residents and faculty, lacking operative/educational opportunities, and disorganization of the rotation. The majority of applicants (60.3 percent) would prefer to return for a standard interview day over interviewing while on rotation. Conclusions: The subinternship experience remains a critical part of the applicant experience when applying to integrated plastic surgery residency programs. The experience on these rotations leaves a lasting impression that is highly variable and influences future recommendations to peers. Rotating students value inclusivity and case volume, and they take note of negative interactions they witness among residents and faculty. These results can help as programs design their subinternship experience for visiting students in the future.